2019
DOI: 10.3389/fimmu.2019.00693
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of Serum IgG4 in Chronic Periaortitis. An Analysis of 113 Patients

Abstract: Objective: Chronic periaortitis (CP) is a rare fibro-inflammatory disorder that incorporates idiopathic retroperitoneal fibrosis, inflammatory abdominal aortic aneurysms, and perianeurysmal retroperitoneal fibrosis. CP is included in the spectrum of IgG4-related disease. Since CP patients rarely undergo diagnostic biopsies, serum IgG4 levels are often used to classify CP as IgG4-related. However, the clinical and prognostic significance of serum IgG4 in CP is unknown. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 33 publications
2
32
0
2
Order By: Relevance
“… 8 Therefore, serum IgG4 levels are of limited value in differentiating IgG4-related RPF from non-IgG4-related IRPF and other inflammatory or neoplastic disorders. On the other hand, because IRPF patients with high serum IgG4 levels more frequently have extra-retroperitoneal fibro-inflammatory lesions, 35 an appropriate systemic screening for other potentially involved sites should be performed in such patients.…”
Section: Laboratory Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Therefore, serum IgG4 levels are of limited value in differentiating IgG4-related RPF from non-IgG4-related IRPF and other inflammatory or neoplastic disorders. On the other hand, because IRPF patients with high serum IgG4 levels more frequently have extra-retroperitoneal fibro-inflammatory lesions, 35 an appropriate systemic screening for other potentially involved sites should be performed in such patients.…”
Section: Laboratory Findingsmentioning
confidence: 99%
“…In comparison with non-IgG4-related IRPF, some studies showed a higher recurrence rate in IgG4-related RPF, 4 while others demonstrated no significant differences in the response to therapy or relapses between the two group. 35 On the other hand, several studies investigated relapse predictors of IgG4-RD not limited to IgG4-related RPF. In type 1 autoimmune pancreatitis (AIP), the pancreatic lesion of IgG4-RD, the risk factors for relapse were reported to include absence of low-dose maintenance glucocorticoid treatment, presence of IgG4-related sclerosing cholangitis, and high immune complex level in long-term observational studies or randomized controlled trials.…”
Section: Prognosismentioning
confidence: 99%
“…However, some patients are refractory, frequently relapsing or have contraindications to glucocorticoids. The anti-CD20 monoclonal antibody rituximab proved efficacious in systemic forms of IgG4-related disease (IgG4-RD) including IgG4-related CP,3 but data on IgG4-unrelated CP are scarce 4–6. In this study, we tested rituximab in CP patients without evidence of IgG4-RD who had relapsing/refractory disease or contraindications to standard-dose glucocorticoids.…”
mentioning
confidence: 99%
“…It was found that IRPF patients got a diagnosis at an earlier age than IgG4-related RPF patients, although the comparison between the two groups fell short of statistical significance. In 2019, Maritati et al [ 23 ] conducted a retrospective observational study including 113 chronic periaortitis (CP) patients, which comprised IRF, IgG4-RPF, and inflammatory abdominal aortic aneurysms patients. They also found an earlier age at diagnosis in CP patients with normal serum IgG4 level.…”
Section: Discussionmentioning
confidence: 99%